Foliar application of Selenium reduced cadmium uptake in Abelmoschus esculentus L. - Mariappan Mahalakshmi; Ammaiyappan Selvam (The Bioscan, 2025)
This study investigated the effects of foliar application of selenium (Se) against Cadmium (Cd) toxicity on the plant growth, biochemical analysis and Cd and Se content in Okra (Abelmoschus esculentus) plant. The experiment was carried out under greenhouse conditions. Cadmium as added to the soil at six concentrations (0, 5, 25, 50, 100 and 250 as CdCl2) mg/kg). For each Cd treatment, three concentration of Se (0, 0.5 and 1.0 μM) were applied as foliar spray. The results showed that increasing Cd concentration in the soil decreased the plant growth as well as increased the antioxidant activity. Application of Se to Cd challenged plants caused an increase in pigment content and enzyme activity. More importantly, low doses of Se reduced the shoot Cd content in the okra plant; however, high level of Se negatively influenced plant growth under Cd toxicity. Overall, Se reduced the cadmium toxicity in plants and the effects were dose-dependent.